Biomaterials - Migonney, Veronique (London, England ; Hoboken, New Jersey : ISTE : Wiley, 2014)
"Discovered in the 20th century, biomaterials have contributed to many of the incredible scientific and technological advancements made in recent decades. This book introduces and details the tenets of biomaterials, their relevance in a various fields, practical applications of their products, and potential advancements of the years to come. A comprehensive resource, the text covers the reasons that certain properties of biomaterials contribute to specific applications, and students and researchers will appreciate this exhaustive textbook"--Publisher's description.
History of biomaterials / Veronique Migonney -- Definitions / Veronique Migonney -- Materials used in biomaterial applications / Geraldine Rohman -- Biocompatibility and norms / Veronique Migonney -- Bioactive polymers and surfaces: a solution for implant devices / Veronique Migonney -- Functionalization of biomaterials and applications / Celine Falentin-Daudre -- Biomaterial structures for anterior cruciate ligament replacement / Cedryck Vaquette -- Animal models for orthopedic applications of tissue engineering / Veronique Viateau, Adeline Decambron, Mathieu Manassero -- Ceramic materials for dental prostheses / Amelie Mainjot -- Dental adhesives / Mathieu Derbanne, Stephane Le Goff, Jean-Pierre Attal -- Glass ionomer cements: application in pediatric dentistry / Elisabeth Dursun, Stephane Le Goff, Jean-Pierre Attal -- List of authors.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Keywords: Biomedical materials; Biomedical materials; Equipment and supplies; Nanostructures; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomedical materials; Biocompatible Materials; Electronic books; Electronic books